Right Bundle Branch Block Like Pattern Recorded in Right Ventricular Endocardial Pacing - Masahiro Ohnuki, MD (Journal of Arrhythmia, 2005)
Right bundle branch block (RBBB) pattern recorded during right ventricular (RV) endocardial pacing should be given special attention in terms of safe RV pacing or lead malposition, e.g. left ventricular pacing or coronary venous pacing, even for patients with no symptoms. Paced electrocardiograms from 47 consecutive patients with a pacemaker implanted were studied. Four patients (8.5%) were found to have RBBB pattern recorded in precordial V1 and V2 leads in the usual 4th intercostal space. All of these patients showed left bundle branch block (LBBB) pattern in limb leads. When precordial V1 and V2 leads in the 5th space were recorded, RBBB pattern changed to LBBB pattern. Biplane chest X-ray film and echocardiogram, especially 3D echo mode, confirmed that tips of pacing leads of the 4 patients were located in the distal RV septum or the apex. RBBB pattern observed during RV endocardial pacing usually represents safe RV endocardial pacing rather than perforation or malposition of pacing leads.